They live under our streets: ant nests (Hymenoptera, Formicidae) in urban pavements - Dijon, Louise; Dekoninck, Wouter; Colinet, Gilles; Francis, Frédéric; Noel, Grégoire (Biodiversity data journal, 2023)
In the context of global insect decline, the urbanisation process plays a key role. However, urban pavements, which are considered to be impervious to biodiversity, can harbour ground-nesting insects under certain conditions. Recent observations have revealed the presence of Formicidae nests under urban pavements. The aim of this work is to determine the species richness of Formicidae nesting under urban pavements in the Brussels-Capital Region (Belgium) and to characterise their nest environment and soil texture. Seven ant species were identified in 120 nesting sites: Lasius niger , Lasius brunneus , Lasius flavus , Lasius fuliginosus , Tetramorium caespitum , Tetramorium impurum and Myrmica rugulosa . Concrete slabs or natural stones with a sandy sub-layer are the main structures in which ants nest. In addition, nests were mainly found under modular pavements with degraded rigid joints. The results of this work highlight the capacity of urban structures to host part of ant biodiversity in cities.